2019
DOI: 10.1016/j.bbmt.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Outcome with a Faster Engraftment of Optimized Haploidentical Hematopoietic Stem Cell Transplantation Compared with Transplantations from Other Donor Types in Pediatric Acquired Aplastic Anemia

Abstract: Haploidentical family donors have been used as an alternative source in hematopoietic cell transplantation for patients with severe aplastic anemia. We evaluated and compared the outcomes of transplantation in pediatric acquired severe aplastic anemia based on donor type. Sixty-seven patients who underwent transplantation between 1998 and 2017 were included. Fourteen patients received grafts from matched sibling donors, 21 from suitable unrelated donors, and 32 from haploidentical family donors. Ex vivo CD3 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…As a result, 32 records were excluded, and 29 studies met the inclusion criteria. The included studies were divided into two groups (MSCs [31][32][33][34][35][36][37][38]; no MSCs [22,24,25,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]) based on whether they applied the MSCs or not. The selection process is illustrated in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…As a result, 32 records were excluded, and 29 studies met the inclusion criteria. The included studies were divided into two groups (MSCs [31][32][33][34][35][36][37][38]; no MSCs [22,24,25,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]) based on whether they applied the MSCs or not. The selection process is illustrated in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…As a result, 32 records were excluded, and 29 studies met the inclusion criteria. The included studies were divided into two groups (MSCs [31][32][33][34][35][36][37][38] ; no MSCs 22,25,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] ) based on whether they applied the MSCs or not. The selection process is illustrated in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…The protocol yielded a high engraftment rate and clinical outcome in the settlement of SAA. Recently, Kim et al optimized haploidentical transplantation using selective T cell depletion and conditioning regimens including low‐dose total body irradiation for enhancing engraftment 49 . They found that haploidentical HSC could rapidly engraft and reconstitute the recipient hematopoiesis and suggested the protocol may be a realistic therapeutic option for pediatric patients with SAA.…”
Section: Discussionmentioning
confidence: 99%